Effect of minor Sc modification on the high-temperature oxidation behavior of near-α Ti alloy. (June 2023) - Zhong, Xiuyang; Deng, Tongsheng; Xiao, Wenlong; Zhong, Ming; Lai, Yunhao; Ojo, Olanrewaju A.
Abstract: In this study, the Ti-6.5Al-2.5Sn-9Zr-0.5Mo-1Nb-1W-0.3Si near-α titanium alloy was prepared by the rare-earth scandium (Sc) microalloying. Influences of Sc on microstructure and oxidation resistance were investigated by cycle oxidation at 650 ℃. Results showed that Sc promotes oxides refinement, adjusts the distribution of Al2 O3 scales and reduces flocculent oxides formation by W-element segregation. However, the addition of Sc in alloy accelerates the dissolution of the residual β phase and the precipitation of silicides, resulting in the cracking of the oxide films and deteriorating the oxidation resistance. Finally, the 0.3 wt% Sc alloy exhibits superior resistance to high-temperature oxidation. Graphical Abstract: ga1 Highlights: Investigated the oxidation resistance of scandium microalloying near-α high-temperature titanium alloys. The microstructure and oxide scale are fined and the segregation of W element is reduced with the addition of Sc. Sc can promote the precipitation of silicide, leading to the oxidation films cracking during oxidation.